Human Development in South Asia 2010/2011 : Food Security in South Asia - Piblished For Mahbub Ul Haq Development Centre (Karachi Oxford University Press, 2011)
Mahbub ul Haq Human Development Centre's 2010-2011 Report on Food Security in South Asia is a valuable contribution towards the conceptual and empirical analysis of food security in South Asia. It analyses the issues of availability and access to food for all South Asians, especially the poor. Ensuring adequate food at affordable prices to all people at all times is the duty of each government. The high prices of food and fuel and economic crisis of recent years have put half a billion South Asians in poverty, millions of children out of school and into work, and over 300 millions of South Asians malnourished. The Report presents critical analyses of food production, distribution, and access for three South Asian countries, India, Pakistan, and Bangladesh. The Report also assesses food security from the perspectives of women and climate change. The Report critically reviews the public food distribution system and social safety net programmes. The Report argues that to give economic growth a human face, South Asia needs to seriously address the effectiveness of its food security initiatives. The objective of all development programmes must be the people and their wellbeing, and food security is the main lifeline of the people.
Include References, Notes and Charts.
Keywords: South Asia -- Food security -- South Asia